Nahwu Madhhab Bashrah on Arabic Language Education in Indonesia - Rizka Widayanti; Nurul Musyafaah; Yelfi Dewi S; Muhammad Afthon Ulin Nuha (Mantiqu Tayr: Journal of Arabic Language, 2023)
Nahwu is one of the critical knowledge of Arabic because nahwu is a rule, parameter of authenticity, and clues to the meaning of Arabic, so knowing nahwu is a must for people who learn Arabic. Nahwu has several madhhabs, each with its characteristics, characters, and opinions. Among the most popular nahwu madhhab is the nahwu Basrah madhhab. The researcher chose the nahwu Basrah madhhab as the theme of this research to reveal the advantages of other madhhabs and the views that emerged from the Basrah madhhab. This research intends to discover several things: 1) the importance of nahwu Basrah madhhab and its development; 2) the influence of nahwu Basrah in learning Arabic. In his research, Researchers in conducting their research used the literature study method, namely by reviewing several books related to themes such as the book al-Kitab, Jami' al-Durus, Syarh ibn Aqil, etc. as well as collecting important information contained by several sources, and detailing it then analyzing it, and finally drawing conclusions. The research findings show that 1) nahwu is the rule by which the ins and outs of Arabic words are known after being arranged on jumlah, and nahwu has a vital role in the use of good Arabic far from mistakes; 2) Among the popular nahwu madhhab is the Basrah madhhab because it has several advantages, including detail in the rules, being careful in the istinbath, and being vital in arguments. Taking advantage of the discussions of nahwu Basrah in learning Arabic is considered an ideal step because the debate is closer to the primary Arabic sources.